Sams teach yourself XML in 24 hours - Morrison, Michael, 1970- (Sams, 2005)
The third edition of Sams Teach Yourself XML in 24 Hours, Complete Starter Kit is everything you need to know about the XML language and how to use it in practical, innovative applications. Understanding the syntax of XML is only a small part of the learning process; understanding how to apply it is the larger part of the learning process, and is the primary focus of this book. It covers a broad range of topics, and wil show you how to use XML to mine data on the web, how to use it to interact with existing data services such as iTunes and Google, and how to use it in applications such as e-books, online speech synthesis, and multimedia. Sams Teach Yourself XML in 24 Hours, Complete Starter Kit, Third Edition will teach you what you need to know to get up and running with XML and more importantly, how to do cool things with it!